Teknik Permainan Kelompok untuk Meningkatkan Perkembangan Sosial Emosional Anak - Delis Nurmilasari; Evi Afiati; Putri Dian Dia Conia (Ma'soem University, 2021)
This study aims to answer whether the application of group games can improve children's social emotional development. This study uses pre-experimental research techniques with one group pre-test post-test design. The method of data collection in the study used an observation instrument. The research subjects consisted of 8 students who had not optimal social-emotional development. The results showed that the socio-emotional development of children in TKQ MALNU increased after being given treatment with group games. Based on the results of the average pre-test and post-test, there is an average difference of 0.74 which defines that group games are effective for improving the social emotional development of children in TKQ MALNU.